2020
DOI: 10.3389/fvets.2020.604477
|View full text |Cite
|
Sign up to set email alerts
|

A Polyphenol-Rich Extract From Entada abyssinica Reduces Oxidative Damage in Cryopreserved Ram Semen

Abstract: The Splinter bean, Entada abyssinica, is widely used in folk medicine. In the current work, we profiled the secondary metabolites from E. abyssinica bark extract using LC-MS and investigated its effect on cryopreserved ram semen. Twenty-eight compounds, including tannins and gallic acid derivatives that prevailed in the extract, were tentatively identified. Results showed that the quality of the post-thawed semen showed a significant improvement when the extract was added to the extender at a concentration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 47 publications
5
16
0
Order By: Relevance
“…Our results are in accord with previous studies demonstrating the harmful effects of thawing on sperm structure and function. Oxidative stress during cryopreservation reduces the reproductive potential of semen by impairing sperm motility, reducing mitochondrial activity, damaging DNA, and activating apoptotic pathways [8,9,29]. Thus, supplementation of semen extender with antioxidants prior to cryopreservation is recommended to facilitate efficient goat breeding [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are in accord with previous studies demonstrating the harmful effects of thawing on sperm structure and function. Oxidative stress during cryopreservation reduces the reproductive potential of semen by impairing sperm motility, reducing mitochondrial activity, damaging DNA, and activating apoptotic pathways [8,9,29]. Thus, supplementation of semen extender with antioxidants prior to cryopreservation is recommended to facilitate efficient goat breeding [30].…”
Section: Discussionmentioning
confidence: 99%
“…To reduce oxidative stress, exogenous antioxidants are frequently added to cryopreservative solutions to sustain semen quality prior to AI [6]. Several studies have confirmed ROS scavenging capacity of various medicinal plant extracts to improve sperm motility and increase fertility rates [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Among the compounds identified was dimethyl caffeoyl galloylglucose, with a retention time of 37.86 min and showed a molecular ion peak at (M–H)− m/z 521 with three daughter ions at 331, 271, and 169. The other compounds were cinnamoyl-O-galloylglucose, p-coumaroyl pyrogalloylgalloylglucose, quercetin galloylglucose, catechin gallate, kaempferol syringyl gallate, gentisic acid dipentoside among others ( Sobeh et al, 2020 ). A new peltogynoid, entadanin and monoglyceride, 1′,26′-bis-[(S)-2,3-dihydroxypropyl]hexacosanedioate along with eight known compounds, were isolated from the stem bark of E. abyssinica .…”
Section: Discussionmentioning
confidence: 99%
“…The other compounds isolated included ursolic acid, quercetin-3-O-β-D-glucosyl (1→4)-α-l-rhamnoside, quercetin-3-O-α-l-rhamnoside (quercitrin), 13,14,15,16-tetranor-3-clerodene-12,18-dioic acid, (8S)-kolavic acid 15-methyl ester, methyl gallate ( Melong et al, 2014 ). These chemical compounds have been reported to possess cytotoxicity, antioxidant and antimicrobial activities ( Sobeh et al, 2020 ; Dzoyem et al, 2017 ). Eight compounds isolated from this plant had low cytotoxicity with cytotoxic concentrations ranging between 20 and 80 μg/ml ( Dzoyem et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…This plant has been used as an extender additive for ram semen cryopreservation [ 56 ]. A wide set of concentrations was used (125, 250, 375, and 500 µg/mL).…”
Section: Herbal Pharmacognosy and Its Use In Andrologymentioning
confidence: 99%